Teaching the English Article System Using the Communicative/Structural Approach - SAADI, Dounia (Journal of Human Sciences, 2016)
Teaching Grammar has moved from focusing on the grammatical structures and combinations using a direct and explicit instruction to emphasizing communication and developing the communicative skills. Like all the grammatical aspects, the English article system is taught following the same perspective. Articles, however, are unstressed, which makes them very difficult, if not impossible, for non-native speakers to detect and eventually learn. Direct explanation of their rules is necessary, as they are hard to be heard and cannot be taught following the Communicative Approach solely. The present paper is intended to show how the Communicative/Structural Approach can be applied in the classroom to teach in general and teach the English article system particularly. We will give a full account of the data obtained during the process of our research which seeks to examine the effectiveness of the Communicative/Structural Approach. We will present the teachers’ views about the usefulness of incorporating the Communicative/Structural Approach in the teaching of articles as well.